The Factors Effective to Economic Growth in Luang Prabang Province - SONGXAYWANG, Yengsouk; SOMSAMONE, Vilayphone; SIPHADA, Vathanaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Study on the factors influencing the province of Luang Prabang's economic growth, including tourist and service income (TS), private sector investment (PSI), public sector investment (PI), export value (EXP), interest rate (ITR), exchange rate (EXR), and currency rate (IFR), produced the following findings: Examining the features of the variable to be evaluated reveals that the variable IFR inflation rate is at, with a statistical significance level of 0.01. The level of first difference in all three equations with the highest level of statistical significance for the variables GDP, TS, PSI, PI, EXP, ITR, and ITR is 0.05, while the level of second difference in all three equations with the highest level of statistical significance for the variable EXR is 0.01. This demonstrates the wonderful features all converters have. The results of the analysis of the factors affecting the economic growth (GDP) of Luang Prabang Province found that: exports (EXP) have a relationship in the same direction with the growth of the economy of Luang Prabang Province in all 6 equations with a statistical significance level of 0.1, 0.05, and 0.01, which test results also show that Equation 1 (the equation that defines all 7 independent variables) is the best conclusion) and found that exports have a positive relationship with GDP equal to 0.079 Meaning: When the export (EXP) increases by 1 unit, the economy (GDP) of Luang Prabang will increase by 0.079 units. Conversely, when exports decrease, the province's economy declines. Private sector investment (PSI) has a relationship in the same direction with the economic growth of Luang Prabang province as well. The interest rate (ITR), the exchange rate (EXR), and the inflation rate (IFR) all have test results that are inversely related to the economy of Luang Prabang province, which means that the factors of interest rate, exchange rate, and inflation rate increase will make the economy of Luang Prabang province lower, which is in line with the hypothesis. Also, the results of the study found that public sector investment factors and tourism income have an inverse relationship with the economy, which is not consistent with the hypothesis without statistical significance.